The O-Na Interaction and Octahedral Geometry around Sodium Moiety in Sodium Salt of N-bromo-4-methylbenzenesulphonamide - Yathirajan, H.S.; Rangappa, K.S.; Nagendra, P.; Mohana, K.N. (Asian Journal of Chemistry, 2010)
The crystal structure of bromamine-T, an important brominating/ oxidising agent, which crystallizes in the triclinic space group PI, has been solved using DIFDIF programme and refined using SHELXL. Bond lengths, bond angles and packing are reported and discussed.